2022
DOI: 10.3389/fpls.2022.820146
|View full text |Cite
|
Sign up to set email alerts
|

Apple Disease Recognition Based on Convolutional Neural Networks With Modified Softmax

Abstract: Accurate and rapid identification of apple diseases is the basis for preventing and treating the apple diseases, and is very significant for assessing disease disaster. Apple disease recognition from its diseased leaf images is one of the interesting research areas in computer and agriculture field. An apple disease recognition method is proposed based on modified convolutional neural networks (MCNN). In MCNN, Inception is introduced into MCNN, global average pooling (GAP) operator is employed instead of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Finally, the 3D coordinates (X, Y, Z) of the apple-picking point in the camera coordinate system are calculated as Equation (10).…”
Section: Coordinate Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the 3D coordinates (X, Y, Z) of the apple-picking point in the camera coordinate system are calculated as Equation (10).…”
Section: Coordinate Conversionmentioning
confidence: 99%
“…In recent years, the rapid development of deep learning has provided new ideas for the visual recognition and localization of harvesting robots [9]. Deep learning can autonomously learn the features of target objects to make up for the shortage of traditional manual feature extraction [10,11]. It is now widely used in various aspects, such as image classification [12,13], image segmentation [14,15], and object detection [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A multi-scale parallel algorithm MP-YOLOv3 was proposed to improve the detection of tomato gray mold based on the MobileNetv2-YOLOv3 model ( Wang and Liu, 2021a ), and the experimental results showed that the improved model has strong robustness in real natural environments. An algorithm based on super-resolution image enhancement ( Zhu et al., 2021 ) and an algorithm combining Inception and an improved Softmax classifier are proposed to detect grape and apple diseases, respectively ( Li et al., 2022 ). Enhancing feature extraction by incorporating DenseNet interlayer density in the YOLOv4 model ( Gai et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars use image processing, such as noise removal, segmentation, and image smoothing threshold method, typical features are extracted, and plant disease recognition models are constructed using convolutional neural networks. They have been applied to recognizing plant diseases, such as apples, peppers, rice, tobacco and vegetables [ [5] , [6] , [7] , [8] , [9] , [10] ], with good recognition results.…”
mentioning
confidence: 99%